Effect of Percutaneous Coronary Intervention (PCI) upon Lung Functions among Patients with Ischemic Heart Disease at Al-Najaf Cardiac Center: Correlation Study (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: The study objectives to detect the effect of angioplasty upon lung functions among Patientswith ischemic heart disease and to find out the relationship between the patients lung functions and theirdemographic and clinical characteristics.Methodology: A descriptive (correlation) design was conducted on the at Al- Najaf center for cardiac surgeryand catheterization. Starting from 1st April 2019 to 1st October 2019. In order to detect the effect of angioplastyon lung function among of patient with ischemic heart disease. A non-probability (purposive) sample of (52)patients, those who admitted to angioplasty unit and coronary care unit without any respiratory diseases.Patients were ischemic heart disease. The patients’ demographic and clinical data collected through theutilization the semi-structured questionnaire and by means of interview technique with the subject, while thepulmonary functions test collected by using spirometer instrument. Data was analyzed by using descriptivestatistic (percentage and Frequencies) and inferential (person s correlation coefficient, independent samplet-test, and paired t-test).Results: The results shows that there is a high significant relationship between the pulmonary functions preand post cardiac catheterization, and most the patients with low PFTs post angioplasty.Conclusions: The present study recommended the nurses whose work at the open Heart Center should teachthe patient undergoing cardiac catheterization breathing exercises to increase the lung capacity as particularand the respiratory system as general and the patient should be given oxygen for at least 60 minutes beforeand after cardiac catheterization to ensure an increase in the oxygen level and perfusion in the body tissues.